Comparative transcriptomic analysis reveals a differential acid response mechanism between estuarine oyster (Crassostrea ariakensis) and Pacific oyster (Crassostrea gigas) - Shen-Tong Wang; Qi Yang; Ming-Kun Liu; Li Li; Wei Wang; Shou-Du Zhang; Guo-Fan Zhang (Ecotoxicology and Environmental Safety)
Ocean and coastal acidification (OCA) poses a significant and rapidly emerging threat to mollusks. The physiological resilience of mollusks to OCA varies considerably; however, the underlying molecular mechanisms remain poorly understood. Seawater in estuaries, being more susceptible to acidification than that in open coastal zones, may enhance the tolerance of resident mollusks to low pH levels. Here, we conducted a comparative analysis between estuarine oysters (Crassostrea ariakensis) and Pacific oysters (Crassostrea gigas) using physiological phenotype and transcriptomic analyses to reveal differential acid-tolerance mechanisms in response to constant pH of 7.8. Our findings indicated that survival and respiration rates of C. ariakensis, which inhabits estuaries with fluctuating pH levels, were higher than those of C. gigas, which inhabits open coastal zones with relative stable pH conditions. Acid-responsive genes identified in C. gigas, including molecular chaperones and immune-related genes, exhibited higher constitutive expression in C. ariakensis under control conditions. Co-expression analyses revealed that C. ariakensis mitigated the effects of low pH by expressing genes involved in ion transporter activity and translation control. C. gigas activated genes associated with glycolipid metabolism while inhibiting cell division during acid stress. These findings suggested that C. ariakensis has evolved into a more energy-efficient regulatory network than C. gigas, incorporating both front-loading and responsive mechanisms to maintain acidbase homeostasis. This study is the first to investigate acid-tolerance differences between mollusks inhabiting estuarine and open coastal environments and provides critical insights into the resilience of mollusks in increasingly acidified oceans.